474. Using telemedicine to provide virtual care for COVID-19 patients at home. (31st December 2020) - Horton, Lucy E; Jenks, Jeffrey D; Bharti, Ajay; Ritter, Michele L; Bordeaux, Kathleen
Abstract: Background: In response to the COVID-19 pandemic in San Diego, California, the Infectious Disease Division at the University of California San Diego established a COVID-19 Clinic dedicated solely to managing patients safely in their homes. This strategy was developed in response to: i) concerns regarding transmission of infection in the healthcare setting, ii) avoiding overwhelming the healthcare system with COVID-19 patients, iii) providing patients with expedited access to specialists, and iv) reducing the burden on the emergency department and urgent care. Methods: The COVID-19 clinic staff is comprised of a dedicated nurse, administrative assistant, and four infectious diseases (ID) physicians who aim to see patients within 24 hours of referral via virtual clinics 5 days a week. An ID physician initially assesses each patient in a direct telemedicine visit and answers their questions, assesses disease severity, provides both symptom management and emotional support, and education about self-isolation and transmission-based precautions. The patients are then triaged to daily nursing phone calls and follow up visits as needed. Results: Over a period of 12 weeks (March 27 to June 16, 2020), the clinic has seen 179 patients. To assess the impact of the clinic, patients are asked to complete a 6-point verbal patients satisfaction survey after their visit. Of the 133 patients who have completed the survey to date, the vast majority reported high satisfaction with their encounters with the COVID-19 physician, with a mean score of 4.8 or higher on all six questions (on a scale of 1 to 5). When asked "Did you feel comfortable talking to your COVID-19 ID physician?" on a scale of 1 to 5, the average score was 4.9. When asked "Did the physician do a good job answering your questions?" the average was 4.9. Patients reported feeling safer after talking with their physician (mean score 4.8), and felt better educated on how to self-quarantine at home (mean score 4.85) and when to seek care from an emergency room, urgent care or hospital (mean score 4.83). Conclusion: The UCSD COVID-19 Clinic demonstrates how telemedicine can be utilized in response to a public health crisis by creating a virtual clinic to provide ID care for patients in their homes. Disclosures: All Authors : No reported disclosures